Ultrastructural evaluation of the effects of 1,25-dihydroxyvitamin D3 on bone of thyroparathyroidectomized rats fed a low-calcium diet. - Weisbrode, S. E. (1978)
Thyroparathyroidectomized rats fed a low-calcium-normal-phosphorus diet were administered 1 or 5 units of 1,25-dihydroxyvitamin D3-(1,25-[OH]2D3) or placebo daily for 7 days. 1,25-(OH)2D3 elevated serum and urine calcium and decreased serum phosphorus. Rats given 1 unit of 1,25-(OH)2D3 had increased numbers of osteoclasts in metaphyseal trabeculae, Ultrastructurally, osteoclasts, osteoblasts, and osteocytes in rats given 1 unit of 1,25-(OH)2D3, were similar to those in rats given placebo. In rats given 5 units of 1,25-(OH)2D3, osteoclasis was markedly increased. Osteoblasts were more numerous and interpreted to be active in matrix production and mineralization. Lamellated electron-dense bodies were observed adjacent to the plasma membranes of less active osteoblasts and were interpreted to be modified matrix. Most osteocytes in rats given 5 units of 1,25-(OH)2D3 were indistinguishable from osteocytes in rats given placebo. However,the pericellular space of some osteocytes in rats given 5 units of 1,25-(OH)2D3 contained electron-dense granular deposits that were interpreted to be calcium phosphate. It is concluded that 1,25-(OH)2D3 is able to significantly elevate serum calcium independent of dietary calcium, parathyroid hormone, and calcitonin primarily by increasing ostoeclasis with minimal dependence on osteocytic osteolysis.